Analysis of Strategies for Establishing Sharia Banks in Minority Areas (Case Study of Dairi District) - Rosalina Simbolon, Linda; Marliyah, Marliyah; Ahmadi Bi Rahmani, Nur (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to find out what strategies are currently being implemented to establish sharia banks in minority areas of Dairi Regency and most importantly to determine the main priority strategies in establishing sharia banks in Dairi Regency. The methods used are SWOT analysis and QSPM. The number of respondents each was 8 people for the SWOT analysis and 5 people for QSPM. Respondents were appointed based on their understanding and mandate or position in the Regional Government or Dairi Regency community, both from academics and practitioners. For the SWOT analysis research results, the strategy quadrant after processing the IFAS and EFAS matrix values ​​is a defensive strategy. This strategy means that it is necessary to minimize weaknesses and avoid threats in the process of establishing a Sharia bank. The weakness is the lack of government support, government alignment is one of the main keys. The threat to Sharia financial institutions is still not well established in the eyes of the public, even though public expectations for LKS are very high. In this way, the main research results can be obtained, namely the main priority strategy that must be carried out is the establishment of a Sharia bank in the minority area of ​​Dairi Regency requires socialization by Islamic Religious Counselors who coordinate and collaborate with the Head of the Dairi Regency Ministry of Religion Office, so that Hajj funds and salaries go through sharia banks and put more emphasis on Religious Instructors, Heads of District KUA, Penghulu efforts to be able to deliver material regarding sharia banking literacy during Friday sermons and also the taklim assembly safari activities which are held every month. Bearing in mind that the instructors also have an Islamic economics material module to be the target material that will be delivered to the congregation assisted by each instructor in each sub-district in Dairi Regency. Like KKN students majoring in Islamic Economics, especially Sharia banking study programs, they can be empowered to convey Sharia banking literacy in Islamic minority areas in collaboration with Islamic organizations in Dairi Regency.